Cellular Therapies in Solid Organ Allotransplantation: Promise and Pitfalls - Shaw, Brian I.; Ord, Jeffrey R.; Nobuhara, Chloe; Luo, Xunrong (Frontiers in Immunology, 2021)
Donor specific transfusions have been the basis of tolerance inducing protocols since Peter Medawar showed that it was experimentally feasible in the 1950s. Though trials of cellular therapies have become increasingly common in solid organ transplantation, they have not become standard practice. Additionally, whereas some protocols have focused on cellular therapies as a method for donor antigen delivery—thought to promote tolerance in and of itself in the correct immunologic context—other approaches have alternatively focused on the intrinsic immunosuppressive properties of the certain cell types with less emphasis on their origin, including mesenchymal stem cells, regulatory T cells, and regulatory dendritic cells. Regardless of intent, all cellular therapies must contend with the potential that introducing donor antigen in a new context will lead to sensitization. In this review we focus on the variety of cellular therapies that have been applied in human trials and non-human primate models, describe their efficacy, highlight data regarding their potential for sensitization, and discuss opportunities for cellular therapies within our current understanding of the immune landscape.